Pengaruh Store Atmosphere, Kualitas Pelayanan Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Exterior Store Surabaya - Jaelani, Syaifullah Yusuf; Arochman, Maqbula (PRAGMATIS, 2025)
This research examines the influence of Store Atmosphere, Service Quality, and Word of Mouth on Purchasing Decisions at Surabaya Store Exteriors. Decision making is a process that involves choosing one of the many available options, and to make this decision several supporting factors are needed. The approach used in this research is a quantitative approach. The problem that is the basis of the research is that there is a gap with previous research related to purchasing decisions. This research gap emerged because of differences of opinion in several previous studies related to purchasing decisions. This research aims to determine the influence of store atmosphere, service quality, and word of mouth on purchasing decisions at the Surabaya Exterior Store. Determination of the sample size was carried out using a non-probability sampling method, with a purposive sampling procedure. The sample taken was eighty respondents with the criteria for respondents being Surabaya residents who were at least seventeen years old and had made direct purchases at the Surabaya Exterior Store. Data was obtained using a questionnaire and processed using multiple linear regression analysis. Based on the results of the hypothesis test that has been carried out, a result can be obtained that the store atmosphere has no significant effect on purchasing decisions at the Exterior Store Surabaya, service quality has a significant effect on purchasing decisions at the Exterior Store Surabaya, word of mouth has a significant effect on purchasing decisions at the Exterior Store Surabaya.